Nutritional compositions and bioactivities of Dacryodes species: a review - Lee, Hong Tee; Bao, Yang; Prasad, Krishnamurthy Nagendra; Ramanan, Ramakrishnan Nagasundara; Sun, Jian; Chan, Eng Seng; Tey, Beng Ti; Azlan, Azrina; Ismail, Amin; Lau, Cheng Yuon; Jiang, Yueming (Elsevier Science Limited, 2014)
Dacryodes species are evergreen, perennial trees with fleshy fruits and belong to the family Buseraseae. Many Dacryodes species are underutilized but are widely applied in traditional folk medicine to treat malaria, fever and skin diseases. The nutritional compositions, phytochemicals and biological activities of Dacryodes edulis, Dacryodes rostrata, Dacryodes buettneri, Dacryodes klaineana and Dacryodes hexandra are presented. The edible fruits of D. edulis are rich in lipids, proteins, vitamins, fatty acids and amino acids. Its extracts (leaf, fruit and resin) exhibit antioxidant, anti-microbial, anti-carcinogenic and other bioactivities. D. rostrata fruit has significant nutrient content, and is rich in proteins, lipids and minerals. These fruits are also highly rich in polyphenols, anthocyanins and antioxidant activities. This comprehensive review will assist the reader in understanding the nutritional benefits of Dacryodes species and in identifying current research needs.